Perlindungan Hukum bagi Konsumen Obat-Obatan terhadap Obat Kadaluwarsa di Apotek - Selviana Teras Widy Rahayu; Nurhayati Nurhayati (Departement of Mathematics Education, 2024)
Current advances in science and technology add to the diversity of life's necessities, including medicine. Consumers must receive appropriate services regarding information on everything contained in the drug and the expiration date of the drug. Consumers can buy medicines at pharmacies or drug stores. A pharmacy is a place where pharmaceutical work is carried out, distribution of pharmaceutical preparations and other health supplies. The pharmacist's duties cannot be separated from the pharmacy, where the availability of medicines that are suitable for drinking is also their responsibility. Therefore, at the end of every month a stock take is held to check the suitability of the medicine, both in terms of storage and the validity period of the medicine. Until now, consumers are still found who suffer losses as a result of pharmacies' negligence in selling expired medicines. Based on Article 3 of Law No. 8 of 1999 concerning Consumer Protection, one of the objectives of consumer protection is to create a consumer protection system. This research aims to determine the form of consumer legal protection for pharmacies that sell expired medicines and the form of pharmacy responsibility. This research is empirical juridical research.